2014
DOI: 10.1073/pnas.1418989111
|View full text |Cite
|
Sign up to set email alerts
|

Replication initiator DnaA binds at the Caulobacter centromere and enables chromosome segregation

Abstract: Significance DnaA is an essential and conserved bacterial protein that enables the initiation of DNA replication. Although it is commonly held that the onset of bacterial chromosome segregation depends on the initiation of DNA replication, we have found that in Caulobacter crescentus , chromosome segregation can be induced in a DnaA-dependent, yet replication-independent manner. The chromosome replication origin, containing essential DnaA binding motifs, resides 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 38 publications
3
39
0
Order By: Relevance
“…There is some precedence for DnaA affecting oriC positioning. In Caulobacter crescentus , which requires a functioning ParABS system for oriC segregation (Mohl and Gober, ; Lim et al ., ), DnaA has been shown to promote oriC segregation independent of its role in initiating DNA replication (Mera et al ., ). This finding raises the interesting possibility that other bacteria might also utilize initiator proteins to facilitate chromosome segregation.…”
Section: Discussionmentioning
confidence: 99%
“…There is some precedence for DnaA affecting oriC positioning. In Caulobacter crescentus , which requires a functioning ParABS system for oriC segregation (Mohl and Gober, ; Lim et al ., ), DnaA has been shown to promote oriC segregation independent of its role in initiating DNA replication (Mera et al ., ). This finding raises the interesting possibility that other bacteria might also utilize initiator proteins to facilitate chromosome segregation.…”
Section: Discussionmentioning
confidence: 99%
“…MipZ inhibits FtsZ polymerization; hence, by associating with ParB, MipZ ends up localized primarily to the polar regions of the Caulobacter , leaving the mid-cell region free for FtsZ polymerization. A recent study suggested that the parS site in Caulobacter interacts not only with ParB, but potentially also with DnaA, providing a link between DNA replication initiation and origin segregation (Mera et al 2014). The model proposed posits that DnaA binds parS sites, somehow altering the structure of the DNA around it in a manner that promotes ParB binding and, consequently, proper segregation.…”
Section: Bacterial Chromosome Segregationmentioning
confidence: 99%
“…Sub-physiological levels of DnaA results in translocation of ori away from stalked pole In C. crescentus, the centromere is the first chromosomal locus to segregate away from the stalked pole [24]. Previous analyses of cells expressing sub-physiological levels of DnaA (not sufficient to initiate replication) revealed a DnaA-dependent and replication-independent segregation of the centromere [31]. Under these sub-physiological levels of DnaA, cells move the un-replicated centromere from the stalked pole to the new pole.…”
Section: Construction Of Indicator Strain With Fluorescently Labeled mentioning
confidence: 99%
“…Based on those results, we asked if the same subphysiological levels of DnaA could also trigger the movement of ori, independently of replication. To reach sub-physiological levels of DnaA in the cell, we used the same vanillate promoter to regulate dnaA expression [31]. Using our indicator strain PM500, we tracked the localization of ori using highresolution microscopy.…”
Section: Construction Of Indicator Strain With Fluorescently Labeled mentioning
confidence: 99%
See 1 more Smart Citation